A Miniaturized Imaging Window to Quantify Intravital Tissue Regeneration within a 3D Microscaffold in Longitudinal Studies. Issue 7 (18th February 2022) - Conci, Claudio; Jacchetti, Emanuela; Sironi, Laura; Gentili, Lorenzo; Cerullo, Giulio; Osellame, Roberto; Chirico, Giuseppe; Raimondi, Manuela Teresa
Abstract: The biocompatibility assessment of biomaterials or the dynamic response of implanted constructs entails inflammatory events primary reflected in cell behavior at the microcirculatory system. Current protocols are based on histopathology which are over 40 years old and require the sacrifice of a huge number of laboratory animal with an unsustainable ethical burden of animal research. Intravital microscopy techniques are actually used to study implantation outcomes in real time. However, no device providing a specific tracking geometry to reposition the field of view of the microscope, for repeated analyses, exists yet. The synthetic photoresist SZ2080 is characterized here, allowing the development and in vivo validation of a miniaturized imaging window, the Microatlas, that, fabricated via two‐photon polymerization, is implanted in living chicken embryos and imaged by fluorescence microscopy 3 and 4 days after the implant. The characterization of their elastomechanical and fluorescence properties highlights planar raster spacing as the most important parameter in tuning the mechanical and spectroscopic features of the structures. The quantification of cell infiltration inside the Microatlas demonstrates its potential as novel scaffold for tissue regeneration and as beacon for 3D repositioning of the microscope field of view and correction of optical aberrations. Abstract : A revolutionary new concept of a miniaturized imaging window is presented, integrating 3D microscaffolds fabricated by two‐photon laser polymerization. The scaffolded window is implanted in the chorioallantoic membrane of living chicken embryos. Its promising potential is demonstrated for time‐lapse high‐resolution imaging analyses in vivo, with simultaneous correction of optical aberration.